2011
DOI: 10.1002/adma.201004114
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Writing of Plasmonic Gold Nanostructures by Electron‐Beam‐Induced Deposition

Abstract: Various nanostructures are directly written by electron-beam-induced deposition using dimethyl-gold(III)-acetylacetonate as the precursor gas. After purification, their potential applications include plasmonic devices and metamaterials. Carbon contamination of the as-written structures can be completely removed by low-temperature ozone treatment, leaving polycrystalline pure gold structures (see figure). This treatment reduces the size of the nanostructures but does not substantially alter their functional sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 24 publications
(26 reference statements)
1
149
0
Order By: Relevance
“…In such a way, local functional nanostructures can be formed without multistep processing, which is necessary in common resistbased electron beam lithography. Among the functional materials that have been fabricated using FEBID are ferromagnetic wires [2][3][4], metallic [5], and graphitic material [6] for low-resistance nanocontacts, as well as granular wires for strain sensors [7], magnetic sensors [8], gas sensors [9], and material with photonic/plasmonic functionality [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In such a way, local functional nanostructures can be formed without multistep processing, which is necessary in common resistbased electron beam lithography. Among the functional materials that have been fabricated using FEBID are ferromagnetic wires [2][3][4], metallic [5], and graphitic material [6] for low-resistance nanocontacts, as well as granular wires for strain sensors [7], magnetic sensors [8], gas sensors [9], and material with photonic/plasmonic functionality [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Free standing single metallic helices with microscale geometrical features, obtained by FIBID process, were presented by Matsui et al [95] More recently, K. Höflich et al [98] showed the fabrication of single gold helices with a base diameter of 50 nm and vertical pitch in the hundred nanometer range by FEBID. Even though no optical activity was reported in these works, applications of these nanostructures in plasmonics were envisioned, and the relevant issue of material purification is also discussed.…”
Section: Optical Activity Of Micro/nanohelices By Focused Ion And/or mentioning
confidence: 99%
“…The precursor used for Pt deposition is Tetrakis(triuorophosphine)platinum, Pt(PF 3 ) 4 (Strem chemicals), a high vapour pressure liquid at room temperature. Due to the sensitivity of this precursor to air and moisture, it was loaded into a peltier-cooled stainless steel bottle in a dry N 2 environment, and sealed using a manual valve.…”
Section: A Platinum Deposition Processmentioning
confidence: 99%
“…FEBID of Pt has attracted more attention than any other material. Platinum nanostructures are of particular interest for applications such as nanoelectronics (as nanowires for interconnects and contacts [3], nanodots for non-volatile memory devices), plasmonic antennas [4] and catalysis (in biosensors and fuel cells). In all of these applications, the resolution, surface area and purity of the deposited material are critical.…”
Section: Introductionmentioning
confidence: 99%